AN ANALYSIS OF ENGLISH STUDENTS’ PARAGRAPHS DEVELOPMENT OF ARGUMENTATIVE ESSAY: A STUDY AT ENGLISH DEPARTMENT OF IAIN IMAM BONJOL PADANG - Gusta, Wienda (journal of RESIDU, 2017)
This research was conducted based on a problem related to the poor ability of the students in writing an argumentative essay at the English Department of IAIN Imam Bonjol Padang. The aim of this research is to find out the students’ ability in writing paragraph development of argumentative essay. This research was a descriptive research. The instrument of this research was using writing task. The population of the research was the third year students at the English Department of IAIN Imam Bonjol Padang which consist of three parallel classes. By using cluster random sampling, the researcher took one class as the sample of this research.From the research findings, it was found that the students’ ability in writing argumentative essay was low. The most mistakes made by the students were in using evidences and in writing sentence precision. It can be concluded that the students still got difficulty in writing a good sentence based on grammatical rules. They also did not know how to write a good concluding paragraph of an argumentative essay.